UTILIZING TIKTOK AS A LEARNING TOOL TO ENHANCE STUDENTS’ ENGLISH-SPEAKING PROFICIENCY AND LEARNING MOTIVATION - Julisa Arya; Nurdin Noni; Hasriani G (State University of Makassar, 2026)
This research aimed to examine the effect of using Tiktok as a learning tool in enhancing students’ English-speaking proficiency and learning motivation. A pre-experimental design with a quantitative approach was employed, involving 28 tenth-grade students from class X4 at SMAN 6 Gowa. The instruments used were a speaking test (pre-test and post-test) and a learning motivation questionnaire. The collected data were analyzed using descriptive statistics to calculate the mean scores, and inferential statistics through a Paired Samples T-Test in SPSS to determine the significance of the differences. The results showed that students’ speaking proficiency improved, with the mean score increasing from 38.46 to 61.43. Furthermore, students’ learning motivation also showed a significant improvement, with the mean score increasing from 40.36 to 62.11. The results of the Paired Sample T-Test indicated a significance value (p-value) of 0.000 (< 0.05) for both variables, confirming that the enhancements were statistically significant.Keywords: TikTok, Speaking Proficiency, Learning Motivation, Learning Tool